PENGARUH ALUNGPEL (AKTIVITAS GULUNG TEMPEL) MENGGUNAKAN KERTAS KOKORU (COLOR CORRUGATED PAPER) TERHADAP KEMAMPUAN MOTORIK HALUS PADA KELOMPOK A - Arum, Sekar; Khotimah, Nurul; Sya’dullah, Achmad; Widayati, Sri (TARBAWI:Journal on Islamic Education, 2025)
This research is based on the problem of children's lack of ability when moving their fingers. This can be seen in writing activities where the fingers are not yet flexible when holding the pencil correctly, folding activities children cannot fold according to the instructions of the teacher and still need help to finish completely. In addition, there is a lack of varied activities to support fine motor development. The purpose of this study was to determine the effect of alungpel (roll paste activity) using kokoru paper on fine motor skills in group A. This study used a Quasi Experimental Design research design with the type of Nonequivalent Control Group Design. The subjects of this study amounted to 18 children in the experimental group and 18 children in the control group. Data collection techniques using observation sheets and documentation. The data analysis technique used was normality test using Shapiro-Wilk and hypothesis testing using Paired sample t-Test. The results of the hypothesis calculation obtained an Asymp. Sig value 0.000 0.05. So in accordance with the basis for making the Paired sample t-Test test decision, it can be concluded that Ha is accepted and HO is rejected.  So from these results it can be interpreted that there is an effect of alungpel (roll and paste activity) using kokoru paper on fine motor skills in group A children at Pratiwi Karang Poh Kindergarten, Tandes, Surabaya.